2011
DOI: 10.1590/s0100-204x2011000900011
|View full text |Cite
|
Sign up to set email alerts
|

Herança da resistência em feijoeiro à murcha causada por Curtobacterium flaccumfaciens pv. flaccumfaciens

Abstract: O objetivo deste trabalho foi determinar a herança da resistência à murcha de Curtobacterium em feijoeiro. Foram realizados dois experimentos: no primeiro, cinco genótipos de feijoeiro, com diferentes reações de resistência à murcha de Curtobacterium, foram cruzados em arranjo dialélico; e no segundo, dois cruzamentos entre genótipos resistentes e suscetíveis - IAC Carioca Aruã x SCS Guará e IAC Carioca Pyatã x Pérola - foram realizados para dar origem às gerações P1, P2, F1, F2, RC1 e RC2. Em ambos os experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
1
Order By: Relevance
“…Several studies in Brazil have consistently shown the reaction of Cff-resistance or high levels of Cff-resistance in the cultivars IAC Carioca Aruã, IAC Carioca Pyatã and IAC Carioca Akytã (Maringoni 2002, Camara et al 2009, Valentini et al 2011a, IAC Carioca Tybatã , Camara et al 2009, Krause et al 2009, Valentini et al 2011a, and IAPAR 31 , Tables 1, 2 and 3). In addition, the cultivars IAC Diplomata, IAC Alvorada, IAC Imperador, IPR Corujinha, IPR Tangará, IAPAR Siriri, BRS Valente and the lines P 5 -4 -4 -1, and C 4 -5 -4 -1 -2 also stood out with high or moderate Cff-resistance levels (Tables 1 and 2), which are so far not described in the literature.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies in Brazil have consistently shown the reaction of Cff-resistance or high levels of Cff-resistance in the cultivars IAC Carioca Aruã, IAC Carioca Pyatã and IAC Carioca Akytã (Maringoni 2002, Camara et al 2009, Valentini et al 2011a, IAC Carioca Tybatã , Camara et al 2009, Krause et al 2009, Valentini et al 2011a, and IAPAR 31 , Tables 1, 2 and 3). In addition, the cultivars IAC Diplomata, IAC Alvorada, IAC Imperador, IPR Corujinha, IPR Tangará, IAPAR Siriri, BRS Valente and the lines P 5 -4 -4 -1, and C 4 -5 -4 -1 -2 also stood out with high or moderate Cff-resistance levels (Tables 1 and 2), which are so far not described in the literature.…”
Section: Resultsmentioning
confidence: 91%
“…Investigating the type of resistance of common bean to Cff, Valentini et al (2011a) studied several generations derived from crosses of IAC Carioca Aruã x SCS Guará and IAC Carioca Pyatã x Pérola and found that it is controlled by genes with an additive effect, involving more than three genes, which are typical characteristics of horizontal resistance (Nelson 1978). Studies by Maringoni (2002) and Souza et al (2006) reported a smaller amount of Cff cells in xylem vessels of resistant than of susceptible common bean genotypes, as well as a characteristic of horizontal resistance, in which defense mechanisms of the host are involved, restricting its colonization by the pathogen (Bergamin Filho et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of genetic variability is determinant for the continuity of studies on inheritance. However, notably, understanding of character inheritance seems to be restricted to univariate analyzes (BERTAN et al, 2009;VALENTINI et al, 2011;CARPENTIERI-PIPOLO et al, 2014). Most characters of agronomic interest are ruled by numerous pairs of alleles, so that the study of a single character is already very complex.…”
Section: Resultsmentioning
confidence: 99%
“…These authors evaluated 73 lines and found only two resistant cultivars (Mouro Piratuba and Vagem Amarela). According to Valentini et al (2011), the low rate of resistant genotypes can be explained by the occurrence of additive and non-additive effects in the inheritance of bacterial wilt resistance. These authors identified more than three resistance genes in two populations resulting from the crosses IAC Carioca Aruã x SCS Guará and IAC Carioca Pyatã x Perola.…”
Section: T Ribeiro Et Almentioning
confidence: 99%
“…According to Valentini et al (2011), the resistance inheritance of this pathogen is polygenic and, according to Souza et al (2006b), Wendland et al (2008), and Torres et al (2009b), the occurrence of genetic diversity and widespread dissemination in the producing regions of Brazil, makes the development of resistance sources even more difficult. For this reason, techniques have been developed to identify this bacterium in common bean crops (Maringoni 2002, Hsieh et al 2005, Herbes et al 2008, as well as to evaluate the resistance of genotypes and lines, with a view to the development of new resistant cultivars (Maringoni 2002, Souza et al 2006a, Theodoro et al 2007).…”
Section: Introductionmentioning
confidence: 99%